"I don't know much about providing pharmaceutical care to people who are transgender": A qualitative study of experiences and attitudes of pharmacists - Swapna Chaudhary; Robin Ray; Beverley D. Glass (Elsevier, 2023)
Background: Globally, with the increased visibility, the number of transgender people accessing healthcare services has risen in the last decade. Although pharmacists are required to provide equitable and respectful care to all patients, their experiences interacting with trans and gender-diverse (TGD) people and attitudes towards the provision of care are largely unknown. Objectives: This study aimed to determine the experiences and attitudes of pharmacists providing care to TGD people in Queensland, Australia. Methods: Within a transformative paradigm, this study used semi-structured interviews conducted in person, over the phone, or through the Zoom app. Data were transcribed and analyzed by applying the constructs of the Theoretical Framework of Accessibility (TFA). Results: A total of 20 participants were interviewed. Analysis revealed all seven constructs across interview data, with affective attitude and self-efficacy being the most frequently coded constructs, followed by burden and perceived effectiveness. The least coded constructs included ethicality, intervention coherence, and opportunity cost. Pharmacists had positive attitudes towards providing care and interacting professionally with TGD people. Prime challenges in delivering care were being unaware of inclusive language and terminology, difficulty building trusted relationships, privacy and confidentiality at the pharmacy, inability to locate appropriate resources, and lack of training in TGD health. Pharmacists felt rewarded when they established rapport and created safe spaces. However, they requested communication training and education to improve their confidence in delivering care to TGD people. Conclusion: Pharmacists demonstrated a clear need for further education on gender-affirming therapies and training in communication with TGD people. Including TGD care in pharmacy curricula and continuous professional development activities is seen as an essential step towards pharmacists improving health outcomes for TGD people.